MAINTENANCE OF FLEXIBLE PAVEMENT BASED ON ITS FUNCTIONAL CONDITION AND STRUCTURAL CONDITION USING BINA MARGA AND AASHTO 1993 METHODS (CASE STUDY: EASTERN TRANS-SUMATRA HIGHWAY MEDAN - LUBUK PAKAM LINK) - YOGA MANDALA PUTRA, M.
Heavy traffic flow and load should be followed by good road pavement performance. Therefore, a periodic evaluation on the road condition providing a good level of service is required. The aim of this study was to conduct a functional and structural evaluations on the flexible pavement of East Trans-Sumatra Highway, that is Medan-Lubuk Pakam Link, as well as to give maintenance recommendations based on the results of this evaluation. The functional evaluation was performed using Bina Marga method that combines the IRI (International Roughness Index) and SDI (Surface Distress Index) values, whereas the structural evaluation of pavement was conducted by analyzing the deflection value from the FWD (Falling Weight Deflectometer) measurement the analysis used the AASHTO 1993 method with SNeff (Structural Number Effective) value and SNf (Structural Number in the Future) value, where the comparison of those two outputs resulted in the SCI (Structural Condition Index) that determines whether a given pavement requires an overlay or not. Based on the results of the Functional Analysis through a combination of the IRI and SDI values, it was revealed that the road condition in each segment was fair and slightly damaged. The structural analysis showed that all segments had an SCI value of less than one, meaning that all segments needs an overlay. The maintenance of the road was performed by combining the functional and structural analysis resulted from the lowest road condition for both analysis (was used as the reference for maintenance). The maintenance was performed using 2 (two) scheme : direct scheme and gradual scheme where the road condition decrease was assessed based on the 5-(five)-year -IRIprediction value using the two schemes which shows that the condition of the road is still good. Meanwhile based on the cost analysis, the total cost difference between the two schemes was Rp. 569.543.317,00, which was more efficient when direct maintenance is carried out. The results of this study showed that the Eastern Trans Sumatra Highway Medan to Lubuk Pakam Link needs a structural treatment in the